Magic fire and other Wagner transcriptions - Marin, Risto-Matti (Finland Alba Records Oy, 2009)
Magic Fireand other Wagner transcriptionsRisto-Matti Marin, piano" Risto-Matti Marin's new release Magic Fire and other Wagner transcriptions includes piano transcriptions by six composers in honor of Wagner anniversary in 2013" Even after his own lifetime, a steady tradition of arrangements of Wagner's music has emerged. By far the most prominent arranger was Wagner's friend and patron Franz Liszt (1811-1886), though many other musicians have succeeded in bringing the world of Wagner's music to life through the medium of the piano.Richard Wagner (1813-1883)1 Jukka Nykänen (b. 1976) Paraphrase on the themes of The Flying Dutchman 6:58Franz Liszt (1811-1886)2 Spinnerlied aus dem Fliegenden Holländer (Spinning Song from The Flying Dutchman) 5:023 Ernest Schelling (1876-1939) Prelude to "Tristan und Isolde" 11:18"""Der Ring des Nibelungen The Ring of the Nibelung:4 Franz Liszt Valhalla 5:58Louis Brassin (1840-1884)5 Siegmunds Liebesgesang (Siegmund's Lovesong) 2:596 Feuerzauber (Magic Fire) 4:097 Carl Tausig (1841-1871) Walkürenritt (The Ride of the Valkyries) 4:558 Louis Brassin Waldweben (Forest Murmurs) 4:599 Ferruccio Busoni (1866-1924) Trauermarsch (Funeral March) 9:14"""10 F. Liszt Tannhäuser Ouvertüre 15:15